Alcohol use in Czech pharmacy students - Trojáčková, Alena; Višňovský, Peter (Central European Journal of Public Health, 2006)
In academic years 2002/3–2004/5, the use of alcohol was investigated by anonymous questionnaire in 1,032 first and third year pharmacy students in the Czech Republic. Frequencies of beer, wine and spirits use, the age of the first contact with alcoholic beverages, the age of the first drunkenness and the frequency of drunkenness in the last month were ascertained. Average age of the first contact with alcoholic beverages was 12.9 years. 40.5% and 10.9% of students reported regular and hazardous drinking, respectively, with significantly higher proportion of men than women. Hazardous alcohol drinking significantly increased between academic years 2002/3 and 2004/5, no significant differences were found in the proportion of non-drinkers and regular alcohol drinkers over the 3-year-period of the survey. Both regular and hazardous drinking patterns were significantly related to the financial situation of the students. Significant associations were also found between alcohol consumption and using of both licit and illicit drugs of abuse.
Keywords: Research Support as Topic; Alcohol Drinking; lidé; pití alkoholu; finanční podpora výzkumu jako téma; průzkumy a dotazníky; studenti farmacie; Students, Pharmacy; Humans; Surveys and Questionnaires